2017
DOI: 10.3389/fpsyg.2017.00752
|View full text |Cite|
|
Sign up to set email alerts
|

Yoga Poses Increase Subjective Energy and State Self-Esteem in Comparison to ‘Power Poses’

Abstract: Research on beneficial consequences of yoga focuses on the effects of yogic breathing and meditation. Less is known about the psychological effects of performing yoga postures. The present study investigated the effects of yoga poses on subjective sense of energy and self-esteem. The effects of yoga postures were compared to the effects of ‘power poses,’ which arguably increase the sense of power and self-confidence due to their association with interpersonal dominance (Carney et al., 2010). The study tested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 68 publications
(112 reference statements)
0
11
0
Order By: Relevance
“…This result contradicts the inconsistent effects of the “power poses” (or expansive postures) found in recent replications of the study by Carney et al [ 20 ] (e.g., [ 44 , 45 ]) or the results of an analysis of different studies made by Simmons et al [ 46 ] that concluded that there is a lack of empirical support for the effects of “power poses”. As De Zabala et al [ 47 ] hypothesized, the inconsistent effects of “power poses” may be related to the lack of manipulation of the lift of the spine and the expansion of the chest. In fact, they compared open and closed front body yoga postures (e.g., emphasizing the lift of the spine and the expansion of the chest) and the expansive and contractive postures used in other studies such as Carney et al [ 20 ], showing that yoga postures (as compared to “power poses”) improved self-esteem through increasing the subjective sense of energy and empowerment.…”
Section: Discussionmentioning
confidence: 99%
“…This result contradicts the inconsistent effects of the “power poses” (or expansive postures) found in recent replications of the study by Carney et al [ 20 ] (e.g., [ 44 , 45 ]) or the results of an analysis of different studies made by Simmons et al [ 46 ] that concluded that there is a lack of empirical support for the effects of “power poses”. As De Zabala et al [ 47 ] hypothesized, the inconsistent effects of “power poses” may be related to the lack of manipulation of the lift of the spine and the expansion of the chest. In fact, they compared open and closed front body yoga postures (e.g., emphasizing the lift of the spine and the expansion of the chest) and the expansive and contractive postures used in other studies such as Carney et al [ 20 ], showing that yoga postures (as compared to “power poses”) improved self-esteem through increasing the subjective sense of energy and empowerment.…”
Section: Discussionmentioning
confidence: 99%
“…The second line of research focuses on postures: Upright postures (UPs) are defined by an erect spine, whereas slumped postures (SPs) are defined by a curved spine and stooped or slouching position. Manipulating the body in this manner is similar to but still different from the manipulation of the expansiveness of the body as done in power posing research (Allen, Gervais, & Smith, 2013) because HPPs do not necessarily include a straight spine (Golec de Zavala, Lantos, & Bowden, 2017). The distinction between poses and postures is supported by the following finding: When people generated words related to prestige 1 (e.g., “good marks,” “diploma”), they changed their posture on a vertical axis, whereas no bodily change was found along the horizontal axis as movement forward or backward (Oosterwijk, Rotteveel, Fischer, & Hess, 2009).…”
Section: Terminology and Theorizingmentioning
confidence: 99%
“…The mechanisms for the impact of yoga in these outcomes are not totally understood. However, previous studies have shown that yoga could be related to lower levels of cortisol, high self‐esteem, lower levels of blood pressure and a better sensation of well‐being and connection with a ‘High Power’ (Carney et al., 2010; Golec de Zavala et al., 2017; Huang et al., 2010). These benefits seem to have the same effect on workers and should be recognized by work organisations and corporations.…”
Section: Discussionmentioning
confidence: 99%